Risk factors for healthcare-associated candidemia in adults hospitalized with SARS-CoV-2 infection - Zachary M. Most; John J. Hanna; Alexander P. Radunsky; Lauren N. Cooper; Christoph U. Lehmann; Trish M. Perl; Richard J. Medford (Cambridge University Press, 2024)
Analyzing data from a national deidentified electronic health record-based data set using a matched case-control study design, we found that antibiotic use and severity of illness were independent risk factors for healthcare-associated candidemia in adult patients hospitalized with SARS-CoV-2 infection. Interleukin-6 inhibitor and corticosteroid use were not independent risk factors.